Analisis Nilai Perusahaan Pada BUMN Sektor Infrastruktur - Kery Utami; Putrie Grace Judhistine Girsang (Jurnal Manajemen dan Organisasi, 2022)
This study was conducted to determine whether Profitability, Dividend Policy, Institutional Ownership, Independent Material Ownership and Audit Quality influence Firm Value when measured using Price to Book Value (PBV). The population of this study is state-owned companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The sample selection technique used is the purposive sampling method and obtained 7 companies that meet the criteria. The data analysis of this research uses panel data regression analysis with Eviews version 12 with a significance level of 5% where the best estimation model chosen is the Fixed Effect Model. The research has gone through the classical assumption test stage and the results obtained that there are no problems of multicollinearity and heteroscedasticity in the research data. The results of this study indicate that Profitability and Institutional Ownership have a positive and significant effect on firm value. The study also stated that the Independent Commissioner has a significant negative effect on firm value. Meanwhile, the dividend policy and audit quality do not affect firm value.